Urinary tract obstruction. Issue 5 (May 2022) - Wilson, Jacob; Farrow, Emily; Holden, Charles
An obstruction may occur anywhere along the urinary tract from the kidney to the urethral meatus. There is a wide range of causes, from benign to malignant, and the ensuing obstruction may develop acutely or more insidiously over weeks to months. Given this variability, symptoms and signs alter depending on the underlying disease process. Knowledge of the anatomy and pathophysiology of the disease process enables prompt recognition and management of common conditions that result in urinary tract obstruction.